The African Lion: A Long History of Interdisciplinary Research - Packer, Craig (Frontiers in Ecology and Evolution, 2019)
Over the past 50 years, lion research has covered a wide range of interdisciplinary topics involving extensive collaborations with scientists from over a dozen different fields. These collaborations have not only led to greater scientific understanding of disease dynamics, impacts of sport hunting on lion populations, and the interactions of lions and their prey, but also resulted in a large-scale disease-control program in rural Tanzania, new hunting policies in several African countries and widespread adoption of camera-traps as a conservation-management tool across Africa.